2020
DOI: 10.1186/s40792-020-00993-9
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal injury related to a personal watercraft: a case report and literature review

Abstract: Background Douche injury is a rare consequence of water recreation activities. Generally, this type of trauma occurs when people fall into the water in a sitting position during high-speed activities such as using a personal watercraft (PWC). Here, we report a rare case of anorectal injury caused by water jets from a PWC during sudden acceleration from rest. Case presentation A 21-year-old male passenger on a PWC fell off backward from the rear seat when the craft suddenly accelerated. He fell into the water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Some authors observed, in appropriately selected patients, that secondary intention healing of extraperitoneal traumatic lesions of the rectum was possible. The conservative management of this type of full-thickness lesion has already been described in the literature after resection of rectal cancer and iatrogenic retroflexion rectal lesions during colonoscopy [12][13][14]. Associated urological injuries are common, with an incidence of approximately 25% in some studies, and although they are more frequent when the trauma is due to penetrating wounds, while approximately 40% of these injuries occurred following blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors observed, in appropriately selected patients, that secondary intention healing of extraperitoneal traumatic lesions of the rectum was possible. The conservative management of this type of full-thickness lesion has already been described in the literature after resection of rectal cancer and iatrogenic retroflexion rectal lesions during colonoscopy [12][13][14]. Associated urological injuries are common, with an incidence of approximately 25% in some studies, and although they are more frequent when the trauma is due to penetrating wounds, while approximately 40% of these injuries occurred following blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Although not common, there are reports in the literature of serious and fatal intra-abdominal injuries secondary to perforation of the vagina, rectum, or bowel after penetration by a PWC hydrostatic jet (Atlas et al, 2015; Etienne et al, 2021; Gill et al, 2011; Katano et al, 2020; Litmanovich et al, 2021; Netz et al, 2015). Upon contact with the perineal area, as the PWC hydrostatic jet overcomes the resistance of the anal or vaginal sphincter, a column of liquid bursts into the body like a bullet and may perforate the vagina, rectum, or bowel (Gill et al, 2011).…”
Section: Water Penetration Into Body Orificesmentioning
confidence: 99%